The Relationship between Health Message Credibility in TikTok Short Video Content and Audience Anxiety - Munajar, Munajar; Wirahadi, Deni; Wijayanti, Yani Tri (SEARCH: Science Education Research Journal, 2026)
The rapid growth of social media, particularly TikTok, has transformed how people access health information, especially among younger generations. While TikTok enables fast and engaging dissemination of health messages, it is also vulnerable to misinformation that may increase audience anxiety. This study aimed to examine the relationship between perceived credibility of health messages in TikTok short-video content and audience anxiety levels in Indonesia. A quantitative approach with a correlational cross-sectional survey design was employed. The sample consisted of 250 active TikTok users aged 18–40 years in Yogyakarta Special Region, Indonesia, who had previously viewed health-related content. Health message credibility was measured based on perceived expertise and trustworthiness of information sources, while anxiety levels were assessed using the GAD-7 scale. Data were analyzed using Pearson correlation and simple linear regression. The findings revealed a significant moderate negative relationship between perceived health message credibility and audience anxiety (r = –0.665; p < 0.05). Higher perceived credibility was associated with lower anxiety levels. These findings emphasize the importance of delivering credible health information through social media to support effective digital health communication.